Enhancement of high temperature performance of cement blocks via CO 2 curing - Meng, Yazi; Ling, Tung Chai; Mo, Kim Hung; Tian, Weihao (Elsevier, 2019)
Carbonation for the curing of cement-based materials has been gaining increased attention in recent years, especially in light of emerging initiatives to reduce carbon dioxide (CO 2 ) emissions. Carbonation method or CO 2 curing is founded on the basis of the reaction between CO 2 and cement products to form thermally stable and denser carbonate, which not only improves the physical and mechanical properties of cement-based materials, but also has the ability to utilize and store CO 2 safely and permanently. This study aims to assess the effect of CO 2 curing technology on the high-temperatures performance of cement blocks. Upon molding, dry-mix cement blocks were cured under statically accelerated carbonation condition (20% CO 2 concentration with 70% relative humidity) for 28 days, followed by exposure to elevated temperatures of 300 °C to 800 °C in order to comprehensively study the principal phase changes and decompositions of cement hydrates. The results indicated that CO 2 curing improved the performance of cement blocks, such as enhancement in the residual compressive strength and reducing the sorptivity. At 600 °C, the scanning electron microscopy (SEM) revealed a denser microstructure while thermal analisis and X-ray diffraction (XRD) analysis also clearly demonstrated that higher amounts of calcium carbonate were present in the cement blocks after CO 2 curing, suggesting better high-temperature performance compared to natural cured cement blocks. In general, an improved high-temperature performance, specifically at 600 °C of the dry-mixed cement blocks was demonstrated by adopting the CO 2 curing technology. This confirms the potential of utilizing CO 2 curing technology in not only improving quality of cement blocks, new avenue for storing of CO2 in construction material can be realized at the same time. © 2019